Comparison of Oral Vancomycin Capsule and Solution for Treatment of Initial Episode of Severe Clostridium difficile Infection. (April 2015) - Bass, Stephanie N.; Lam, Simon W.; Bauer, Seth R.; Neuner, Elizabeth A.
Objective: Vancomycin is recommended as a first-line therapy for severe Clostridium difficile infection (CDI). Due to the high cost of commercially available vancomycin capsules, hospitals frequently compound oral solution despite a lack of data comparing outcomes. This study was conducted to determine treatment outcome differences based on oral vancomycin formulation. Methods: Medical charts of 76 patients with an initial episode of severe CDI receiving oral vancomycin as a commercially available capsule or a compounded oral solution for at least 72 hours were retrospectively reviewed. The primary objective was to compare the time to clinical cure of CDI. Results: Baseline characteristics between groups were similar except for the median lactate, which was higher in compounded oral solution group (1.5 vs 0.6 mmol/L, P < .001). There was no difference in clinical cure at day 10 (64% solution vs 59% capsules, P = .664). Median time to clinical cure was 8 days for solution and 7 for capsules ( P = .597). After adjustment, the hazard ratio of time to clinical cure for solution compared to capsules was 1.15 ( P = .69). No significant differences in mortality, recurrence, or complications were noted. Conclusion: Formulation of oral vancomycin did not impact treatment outcomes in this retrospective study.